2019
DOI: 10.5194/isprs-archives-xlii-3-w9-83-2019
|View full text |Cite
|
Sign up to set email alerts
|

Calculation and Analysis on Scattering Characteristics of Non-Spherical Particles of Haze

Abstract: Abstract. The light scattering characteristics of sulfate, one of the main pollutant particles in haze, are calculated by T-Matrix method at a target wavelength of 550 nm. The variation between shape factors (such as effective radius and aspect ratio) and scattering phase functions with different types and shapes are analysed in small scale range. The influence of shape factors on scattering cross section and depolarization ratio of particles are also discussed. Results show that the shape of particles has gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…M. Ji et al analysed the light scattering properties of sulphate particles at a target wavelength of 550 nm using T-matrix calculations. The results showed that the difference in the spatial distribution of the scattered light field mainly depends on the particle shape, that spherical particles hardly affect the polarisation of the light wave, and that the average deconvolution ratio and the scattering cross section of non-spherical particles vary continuously with the particle aspect ratio and the particle size range, so that the deconvolution of the scattered light can be used to distinguish the shape of certain particles under certain conditions [9].…”
Section: Introductionmentioning
confidence: 99%
“…M. Ji et al analysed the light scattering properties of sulphate particles at a target wavelength of 550 nm using T-matrix calculations. The results showed that the difference in the spatial distribution of the scattered light field mainly depends on the particle shape, that spherical particles hardly affect the polarisation of the light wave, and that the average deconvolution ratio and the scattering cross section of non-spherical particles vary continuously with the particle aspect ratio and the particle size range, so that the deconvolution of the scattered light can be used to distinguish the shape of certain particles under certain conditions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have typically utilized haze and water spray scattering environments for simulations and experiments [1][2][3][4][5][6]. K. Chamaillard et al investigated the effect of the shape of dry sea salt particles on the detection of particulate light scattering.…”
Section: Introductionmentioning
confidence: 99%